Comparative effects of 4-Cl-IAA and kinetin on photosynthesis, nitrogen metabolism and yield of black cumin (Nigella sativa L.) - Shah, Shoukat Hussain (Acta Botanica Croatica, 2011)
The leaves of 40-day old plants of black cumin (Nigella sativa L.) were sprayed with 10–7, 10–6, 10–5M4-Cl-IAA, and 10–6, 10–5 and 10–4Mkinetin. Both the hormones improved vegetative growth, photosynthetic efficiency and seed yield of the test plants as compared to deionized water (control). However, 10–6 M 4-Cl-IAA was most prominent in its effect, generating 42, 30, 40, 41 and 51% higher values for carbonic anhydrase, nitrate reductase, net photosynthetic rate, leaf protein content and dry mass respectively, as compared to the control in 70-day old plants. Similarly, capsule number and seed yield per plant were elevated by 41 and 43% over the untreated control at harvest (130 days after sowing) following the same treatment. Overall, the auxin showed a higher efficiency than kinetin in all treatment concentrations.